Consumers are unaware about European legislation on communication of the health benefits conveyed by claims: An empirical survey - Antonella Di Fonzo; Claudio Liberati (Italian Review of Agricultural Economics (REA), 2020)
This paper investigates how consumers knowledge of the EC list (reg. (EU) 432/2012) can affect their understanding of health claims (HC). Despite the existence of a rigorous regulation on the communication of health benefits attributed to functional foods (reg. (EC) 1924/2006), there are still doubts about the efficacy of legislation. In fact, the information conveyed by HC does not always reach the consumer in a clear and understandable way, making the consumer skeptical. This paper proposes an empirical analysis to verify if this effect could be mitigated in case that the consumer knew the European register of HC. The results show how consumers skepticism is linked to trust and assessment problems that contribute to limit the HC efficacy and provide new elements to improve the health benefits regulation.
Keywords: Q01; Q1; M31; D12; 330; functional food; regulation; health claims; credence goods; food choice